Pengaruh Dividen dan Biaya Keagenan terhadap Nilai Perusahaan (Model Komparatif pada Perusahaan yang Menerapkan Corporate Governance dengan Intensitas Tinggi dan Rendah) - Fadah, Isti (Jurnal Aplikasi Manajemen, 2013)
The aims of the research are (1) to analysis the effect of dividend payment on corporate value, and (2) to analyze the effect of agency cost on corporate value. The sampling technique is purposive sampling. Secondary data is used in this research. It is from financial report like balance sheet, financial statement, and cash flow report. The data are obtained from Indonesian Stock Exchange database. Data analysis usesstructural equation model (SEM), because the model has a ladder causality relationship and is able to analyze several variables relationship consisting of ownership structure, agency cost, risk, dividend payment and corporate value as latent variables. The result of the analysis for corporates that aplied GCG with high intensity shows that ownership structure and free cash flow have significant effect on agency cost;besides, dividend payment and agency cost have significant effect on corporate value. For corporates that aplied GCG with low intensity show that ownership structure and free cash flow have significant effect on dividend payment.